2006
DOI: 10.1098/rspb.2006.3683
|View full text |Cite
|
Sign up to set email alerts
|

New insights into neuropeptide modulation of aggression: field studies of arginine vasotocin in a territorial tropical damselfish

Abstract: The neuropeptides arginine vasotocin (AVT) and arginine vasopressin are key modulators of affiliation and aggression among non-mammalian and mammalian vertebrates, respectively. Here, we explored AVT's effect on aggression in a wild population of beaugregory damselfish, Stegastes leucostictus, a highly territorial species. Aggression by territorial males towards 'intruders' (bottled fishes) was assessed before and after each male received intramuscular injections of either AVT, Manning compound (an AVT V1a rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
97
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(110 citation statements)
references
References 46 publications
11
97
2
Order By: Relevance
“…Isotocin, a paralog of arginine vasotocin (AVT) and a homolog to mammalian oxytocin, is a candidate for the regulation of dominant and aggressive behavior in Julidochromis. Although the few studies that have investigated a role for isotocin in aggressive behavior have found no correlation (Santangelo and Bass, 2006), its expression pattern here suggests otherwise. Parvalbumin, another identified gene in the dominance M. Schumer, K. Krishnakant and S. C. P. Renn module, is expressed in GABAergic neurons (de Almeida et al, 2005), which have been linked to aggressive behavior in a number of mammalian species.…”
Section: Identified Dominance-related Genesmentioning
confidence: 69%
“…Isotocin, a paralog of arginine vasotocin (AVT) and a homolog to mammalian oxytocin, is a candidate for the regulation of dominant and aggressive behavior in Julidochromis. Although the few studies that have investigated a role for isotocin in aggressive behavior have found no correlation (Santangelo and Bass, 2006), its expression pattern here suggests otherwise. Parvalbumin, another identified gene in the dominance M. Schumer, K. Krishnakant and S. C. P. Renn module, is expressed in GABAergic neurons (de Almeida et al, 2005), which have been linked to aggressive behavior in a number of mammalian species.…”
Section: Identified Dominance-related Genesmentioning
confidence: 69%
“…Our study shows that this preference hinges critically on the timing of complex call production: females prefer males that produce a complex call. All males are capable of producing complex calls but choose to do so depending on the social environment, with complex calls more commonly produced (1) during bouts of vocal competition between neighbouring males (Bernal et al 2009), (2) in the presence of females (K. L. Akre, personal communication), (3) when predation risk is perceived to be lower (Tuttle et al 1982;Jennions & Backwell 1992;Phelps et al 2007) and (4) when injected with arginine vasotocin (Kime et al 2007), a neuropeptide that modulates social behaviour in many species (Moore & Miller 1983;Boyd 1994;Chu et al 1998;Marler et al 1999;Sanantgelo & Bass 2006). We show that the continued production of complex calls is critical when females are assessing and approaching potential mates, and therefore, males should be under selection to maintain complexity during peak female attendance at the chorus or when females are detected directly.…”
Section: Discussionmentioning
confidence: 99%
“…Vasopressinergic neuropeptides like AVP/AVT, and the serotonergic systems have been identified as crucial determinants in the regulation of aggression (Trainor et al, 2009), including coral reef teleosts (Semsar et al, 2001). Indeed, AVT has been shown to increase aggression in a dose dependent manner in Stegastes leucosticus, a tropical year-round territorial damselfish (Santangelo and Bass, 2006). Fluoxetine, a serotonin reuptake inhibitor which enhances serotonergic neurotransmission, caused a decline in aggressive behavior in Thalassoma bifasciatum (Perreault et al, 2003).…”
Section: Year-round Territorial Aggression and Androgensmentioning
confidence: 99%